A new case series of Crisponi syndrome in a Turkish family and review of the literature. Issue 2 (April 2017) - Bayraktar-Tanyeri, Bilge; Hepokur, Mervenur; Bayraktar, Suleyman; Persico, Ivana; Crisponi, Laura
Abstract : Crisponi syndrome/cold-induced sweating syndrome (CS/CISS) is a rare autosomal recessive disorder with a complex phenotype, reported in the neonatal period for CS and in the evolutive one for CISS. The syndrome usually manifests at birth. The aim of this study was to report on three new patients with CS and review the Turkish patients. We report here on three patients from two related families harboring a homozygous mutation in the cytokine receptor-like factor-1 (CRLF1) gene. DNA samples of the three patients and their parents were subjected to a mutational analysis of the CRLF1 gene at the Institute of Biomedical and Genetic Research – National Research Council, Cagliari (Italy). Direct sequencing of the nine coding exons and surrounding intronic regions of CRLF1 was performed using specific primers. All three patients were found to be homozygotes for the mutation c.708_709delinsT, which leads to a frameshift in the second fibronectin type III domain (p.Pro238Argfs*6). CS should be considered in the differential diagnosis of newborns with muscle contractions, feeding and swallowing difficulties, dysmorphic facial findings, camptodactyly, and hypertermia. Neonatologists must be aware of this syndrome that, although very rare worldwide, has a higher prevalence in Turkey.